PENGEMBANGAN E-MODUL BERBASIS KEMAMPUAN BERPIKIR KREATIF MENGGUNAKAN FLIP PDF PROFESSIONAL PADA MATERI KOLOID DI SMAN 4 KOTA BENGKULU - Nurhamidah; January Prayogi; Salastri Rohiat (ALOTROP, 2022)
This study aims to determine the feasibility and students' responses to an e-module based on creative thinking skills using flip pdfprofessionalprogram on colloidal material. This research was a research and development (research and development) that adapts from the Borg & Gall model which is limited to the seventh stage, namely product revision. The sample in this study were students of class XI MIPA 1 SMA N 4 Singaran Pati,Bengkulu City with a total sample of 33 people. The sample selection in this study used a purposive sampling technique. The data in this study were obtained from interviews, material and media validation questionnaires, and student response questionnaires. The results of the validation test of e-module materials and media obtained values ​​of 4.25 and 4.60 which are included in the "very valid" category because they are in the range of values ​​of 4,2< 5. The results of the e-module student response test at school was 4.35 which is included in the "very interesting" category because it is in the value range of 4,2< 5. So it can be concluded that the e-module based on creative thinking on colloidal material developed is feasible to be used in the learning process.